CAN RELIGION PREVENTS CORRUPTION? THE INDONESIAN EXPERIENCE - Kartini Laras Makmur (AL WASATH Jurnal Ilmu Hukum, 2020)
Researches on Anti-Corruption have found that politics, economics, and culture have a relation to corrupt practices. However, what about the influence of religion on corruption? Recently, there is an increasing interest in understanding the relationship between religion and corruption; could religion prevent corruption? This paper discusses the effect of religiosity on bureaucratic corruption in Indonesia. The results show that corrupt practices are negatively associated with religious heritage, signifying that religious culture takes a positive role in delimiting corrupt practices of government officials since religion has an influence on the normative anti-corruption paradigm. This paper also finds the negative relationship between religion and corruption is weaker for people who had experience requested by an official to paid illicit payment, which identifies the substitution chance of religious ethic and law enforcement in curbing corruption. Given the very few studies and limited data resources in the context of Indonesia, this paper is only a tentative study to contributes to the discussion of religion and corruption relations.